CLIMATE CHANGE AND WATER POTENTIAL OF THE PAMIR MOUNTAINS - Alexander F. Finaev; Liu Shiyin; Bao Weijia; Jing Li (Geography, Environment, Sustainability)
The Pamir region supplies water for most countries of the Central Asia. Discussions and arguments with regard to reduction of water resources related to climate change are popular today among various governmental and international institutions being a greatconcern for modern society. Probable decrease of the Pamirs runoff will affect downstreamcountries that can face water deficiency. However, there is no scientific rationale behindsuch disputes. The Pamir region is a remote, high-mountainous and hard-to-access area with scarce observation network and no reliable data. It is not sufficiently investigated in order to perform any assessment of climate change. This article represents results of study of climate parameters change (such as temperature, precipitation and river discharge) in the Pamirs. The study area covers all countries included in this mountain region (Tajikistan, China, Afghanistan and Kyrgyzstan). Observation records, remote sensing data and GIS modeling were used in the present work. Chronological data series were divided into two equal time intervals and were treated as climatic periods. Further analysis of climate change helped to estimate its influence on change of water potential in the Pamirs. The paper considers issues of liquid and solid precipitation change in the study area.